MENSEJAHTERAKAN MASYARAKAT DENGAN ADANYA KEBERSAMAAN DAN MELAKSANAKAN BAKTI SOSIAL PEMBERSIHAN LINGKUNGAN MASYARAKAT DESA SIMARTUGAN - Jhon Sufriadi Purba; Sri Devi Marchelina Siahaan; Moses Novianus Purba; Tambos Sianturi; Winfrontstein Naibaho (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Simartugan Village is a place that has a lot of potential that can be developed both from natural resources and human resources. The problem found in Simartugan village is the lack of cleanliness in the village. Therefore, the work program of the UHKBNP KPPM group located in the village of Simartugan is for the welfare of residents regarding the importance of maintaining cleanliness in the community environment. The work program created aims to create a clean and healthy environment in addition to helping each other. The method used is in the form of Environmental Cleaning Social Service activities by carrying out Cooperation. The Environmental Cleaning Social Service activity is an activity where with this activity we can strengthen our kinship. Mutual cooperation between residents carried out by students is to create a sense of love, a sense of mutual assistance, a sense of mutual care for students in the wider community who are in need of their helping hand. The activity method used is observation and participation. The observation was carried out by checking the location of Mutual Cooperation in the hamlet 1 – hamlet 6 environment of Simartugan village. The Gotong-royong activity in Simartugan Village, Pegagan Hilir District, Dairi Regency was carried out in a structured manner starting from the preparation stage to the implementation of the activity involving students of Community Service Program of HKBP Nommensen Pematangsiantar University, Pegagan Hilir District and several village officials who intervened directly